Training-induced changes in physical performance can be achieved without body mass reduction after eight week of strength and injury prevention oriented programme in volleyball female players - Lehnert, M; Sigmund, M; Lipinska, P; Vařeková, R; Hroch, M; Xaverová, Z; Stastny, P; Háp, P; Zmijewski, P (Biology of Sport, 2017)
The purpose of the study was to analyse the changes in muscle strength, power, and somatic parameters in elite volleyball players after a specific pre-season training programme aimed at improving jumping and strength performance and injury prevention. Twelve junior female volleyball players participated in an 8-week training programme. Anthropometric characteristics, isokinetic peak torque (PT) single-joint knee flexion (H) and extension (Q) at 60º/s and 180º/s, counter movement jump (CMJ), squat jump (SJ), and reactive strength index (RSI) were measured before and after intervention. Significant moderate effects were found in flexor concentric PT at 60º/s and at 180 º/s in the dominant leg (DL) (18.3±15.1%, likely; 17.8±11.2%, very likely) and in extensor concentric PT at 180º/s (7.4%±7.8%, very likely) in the DL. In the non-dominant leg (NL) significant moderate effects were found in flexor concentric PT at 60º/s and at 180º/s (13.7±11.3%, likely; 13.4±8.0%, very likely) and in extensor concentric PT at 180º/s (10.7±11.5%, very likely). Small to moderate changes were observed for H/QCONV in the DL at 60º/s and 180º/s (15.9±14.1%; 9.6±10.4%, both likely) and in the NL at 60º/s (moderate change, 9.6±11.8%, likely), and small to moderate decreases were detected for H/QFUNC at 180º/s, in both the DL and NL (-7.0±8.3%, likely; -9.5±10.0%, likely). Training-induced changes in jumping performance were trivial (for RSI) to small (for CMJ and SJ). The applied pre-season training programme induced a number of positive changes in physical performance and risk of injury, despite a lack of changes in body mass and composition. CITATION: Lehnert M, Sigmund M, Lipinska P et al. Training-induced changes in physical performance can be achieved without body mass reduction after eight week of strength and injury prevention oriented programme in volleyball female players. Biol Sport. 2017;34(2):205-213.